Social Networks to Rescue COVID-19 Education: Learners' Awareness of Social Networks in Aiding Education - Govender, Reginald; Govender, Desmond (International Journal of Innovative Research and Scientific Studies, 2022)
Governments around the world have temporarily closed educational institutions in an attempt to contain the spread of the novel coronavirus (COVID-19). This has culminated in the largest school disruption in recent history. This study explored learners’ awareness of using smart educational systems (social networks) to support remote learning (e-learning). The study examined three constructs: Motivation, Active role, and Interaction, based on the theory of Connectivism. These constructs contributed to the development of a survey used to gather perspectives on social networks in education from a group of Business Studies learners in a South African high school. Data was collected from a sample of Business Studies learners (n=133) just before the COVID-19 pandemic. The results show there was an awareness of the use of social networks in education among learners. Therefore, social networks had the potential to support distance education during the pandemic.